2009
DOI: 10.1038/ng.352
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation at the DEP1 locus enhances grain yield in rice

Abstract: Grain yield is controlled by quantitative trait loci (QTLs) derived from natural variations in many crop plants. Here we report the molecular characterization of a major rice grain yield QTL that acts through the determination of panicle architecture. The dominant allele at the DEP1 locus is a gain-of-function mutation causing truncation of a phosphatidylethanolamine-binding protein-like domain protein. The effect of this allele is to enhance meristematic activity, resulting in a reduced length of the inflores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
806
2
34

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 907 publications
(860 citation statements)
references
References 21 publications
18
806
2
34
Order By: Relevance
“…And the increased diameter of both culm and panicle may help to enhance the potential in lodging and fertilizer resistance. Genetic studies of erect panicle varieties derived from Balilla and other mutants have identified panicle erectness genes, such as DEP1/qPE9-1, EP2, and EP3, in recent years [10][11][12][14][15][16]. Unlike dep1, the number of spikelets and primary and secondary branches was almost the same in dep2 compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…And the increased diameter of both culm and panicle may help to enhance the potential in lodging and fertilizer resistance. Genetic studies of erect panicle varieties derived from Balilla and other mutants have identified panicle erectness genes, such as DEP1/qPE9-1, EP2, and EP3, in recent years [10][11][12][14][15][16]. Unlike dep1, the number of spikelets and primary and secondary branches was almost the same in dep2 compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…The genetics of sink size (e.g., grain size and grain number) has been well analyzed in rice plants, and several QTLs controlling grain number per panicle and grain size have been identified (Ashikari et al 2005;Fan et al 2006;Song et al 2007;Shomura et al 2008;Huang et al 2009). On the other hand, genetic analyses of factors affecting source capacity, such as photosynthetic rate, have been limited, probably because of the need for time- C1006 G2009 C479 C383 G1068 C145 R646 R1440 R2394 R2677 R1245 C847 R1789 G379 C596 C924 C213 8 R1943 G278 C277 C1121 C1107 G104 C347 R1394A G1073 S10622 G187 R2382 R202 S14074 G1149 R2662 R1963 9 C711 G36 R1164 R1751 G385 R2272 S1057 C609 C1263 C570 C506 G1445 10 C701 S2083 R2174 C148 R1629 C1166 R2447 R3285 C1286 R1877 R844 G2155 R716 C16 C809 C405 11 G24A R77 R3202 C794A S1057 C410 C477 G320B G320A C535 G44 C3 R728 G257 C1172 S723 C50 G1465 C82 C950 G181 12 G24B R1957 C1336 R2672A R367 R3375 R...…”
Section: Discussionmentioning
confidence: 99%
“…Central to this variation are unique branching patterns that contribute directly to traits such as grain yield, harvestability, and hybrid seed production (Kellogg 2007;Huang et al 2009;Sreenivasulu and Schnurbusch 2012;Ishii et al 2013). Among grasses, inflorescence architecture is diverse, yet characterized by a unique morphology, where flowers are borne on specialized short branches called spikelets (Kellogg 2007;Thompson and Hake 2009).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%